Researching in atmospheres: video and the 'feel' of the mundane. (August 2015) - Pink, Sarah; Leder Mackley, Kerstin; Moroşanu, Roxana
In this article, the authors advance recent discussions of atmospheres by developing an approach that builds theory in relation to methodological understandings of how and what we can we know about atmospheres. They argue that, in order to be able to understand the significance of an atmosphere empirically, a theory is needed that can account for the specificities of particular atmospheres that are generated in the context of actual research sites, the everyday contingencies in relation to which they shift and change, and the different ways in which they might be perceived. To do this, they propose that atmospheres should be understood as part of and as emerging from within environments Simultaneously, to be able to build theory thorough empirical research, an approach is needed that is capable of researching how atmospheres are made and sensed by people in mundane everyday moments, and how they are generative of sensory, affective and empathetic forms of engagement. Situating video recording, like atmospheres, as emerging from within environments, the authors show how video ethnography can enable us to build the theoretical and empirical ambitions of this field of investigation.